Meningkatkan Branding Kain Tenun Songket Khas Desa Mandi Angin Inderalaya Selatan Ogan Ilir - Pratiwi, Diany Putri; Febrianza, M; Chaniago, Ade Indra (Yayasan Kawanad, 2022)
Indonesia has a variety of cultures. One of the cultures of Indonesia is Songket woven fabric. Songket woven cloth is a traditional cloth originating from the island of Sumatera. Songket Palembang is one of the cultures from South Sumatera which has been designated as an intangible cultural heritage of Indonesia in 2013 by the ministry of education and culture. Palembang songket woven fabric is a culture that is used in a variety of certain traditional activities, such as weddings. This paper aims to increase knowledge and improve the branding of songket woven fabrics mainly in Mandi Angin village, South Inderalaya District, Ogan Ilir Regency. The method used in this paper is a descriptive method with the main data collection of the author in this paper obtained through direct observation or observation in the field, interviews conducted by recording the results of interviews or by using a voice recorder to informant and documentation by taking photos related to writing in the field. The result of the paper is to improve the branding of the songket woven fabric of Mandi Angin Village, as a characteristic of Mandi Angin Village, South Inderalaya District, Ogan Ilir Regency